“Restrained eating” vs “dieting”: how are they associated with body weight status, eating behavior and eating frequency among Polish adolescent - Bajerska, Joanna; Pieczyńska, Joanna; Woźniewicz, Małgorzata; Chawłowska, Ewelina; Łagowska, Karolina; Biskupska, Maria (Progress in Nutrition, 2022)
Aim: This study aimed to assess how dieting and dietary restraint were associated with body weight status and eating frequency of certain food groups in a sample of 874 healthy Polish adolescents and young adults aged 16-18 years. Methods: Anthropometric parameters were measured using standardised techniques and instruments. The validated food frequency questionnaire was used to assess habitual dietary intakes. Eating behaviour was assessed with the Three-Factor Eating Questionnaire. The physical activity was assessed by the International Physical Activity Questionnaire. Results: The odds ratio (OR) for overweight and obesity was 1.81 (CI95%:1.22;2.70, p=0.003) times higher among current dieters than nondieters. The odds of being overweight or obese were significantly lower with female sex [OR=0.40 (CI95%:0.27;0.59, p